Laserstrahljustieren mittels Aktoren - Entwicklung von Konzepten und Methoden für die rechnerunterstützte Modellierung und Optimierung von komplexen Aktorsystemen in der Mikrotechnik - Wurm, Thomas (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2004)
Laser adjustment with actuators – Development of a modular system for the computer aided design and optimisation of complex actuator geometries The increasing miniaturisation in the industrial production of electronic, optical and micro mechanical components requires an improved assembly technology. Sub-micrometer adjustment hast to be obtained within seconds. Laser adjustment offers a new approach to the assembly process of micro-parts with tolerance areas in the sub micrometer range. The application of laser adjustment requires an optimised construction of an actuator geometry. Therefore, the construction of an actuator geometry, or even such a single geometric element, makes great demands on the designer. The technical requirements on the actuators are determined by the number of necessary degrees of freedom, the maximum and the minimum adjustment area. This research aims at developing a concept and an implementation of a modular system to design and compute an actuator geometry for the respective problem. Therefore, the actuator system is described as a kinematic chain of single geometric elements. Additionally, a construction catalogue has been developed, in which fundamental actuator geometries are classified. This construction catalogue can be accessed while developing the geometry. Using the computational assistance of the modular system, the complex task of actuator design will be much more efficien